(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت الدراسة إلى تحديد مدى إدراك المراجع في سورية للعوامل المؤثرة على خطر الرقابة الداخلية. لذلك تم إجراء مسح ميداني باستخدام الاستبانة على عينة من المراجعين الذين استطاع الباحث التواصل معهم, حيث تم توزيع /56/ استبانة, استرجع منها /34/ استبانة. أظهرت النتائج أن هناك موافقة من قبل أفراد العينة المدروسة على البنود المعبرة عن الجوانب الثلاثة لخطر الرقابة الداخلية (البيئة الرقابية, النظام المحاسبي, الإجراءات الرقابية), مع التنويه إلى وجود نوع من التحفظ من قبل هؤلاء المراجعين حول بعض الفقرات المعبرة عن البيئة الرقابية, والمتمثلة بطرق تحديد السلطة والمسؤولية, و سياسات إدارة الأفراد والبرامج التدريبية التي توضع لهم, والمؤثرات الخارجية التي تؤثر على عمليات المنشأة وسياساتها. The study aims to examine the extent of Syrian Auditor awareness for the factors affecting the Internal Control Risk. For this purpose, a field survey conducted using a questionnaires a sample of Auditors with whom the Researcher had contact. A number of \56 questionnaires were distributed, out of which \34 were filled and returned back to the Researcher. Data analysis showed the following: There is a consensus on the clauses covering the three aspects of the Internal Control Risk : (Control Environment, Accounting System, Control Procedures); additionally, there is a kind of reservation by those auditors about many statements regarding to the Control Environment which are: methods of determining authority and responsibility, policies of individuals management and training programs set for them, and external influences affecting enterprise’s operations and policies.